1991
DOI: 10.1128/jvi.65.10.5381-5390.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a transactivating function mapping to the putative immediate-early locus of human herpesvirus 6

Abstract: Sequencing studies have indicated that the unique component of the human herpesvirus 6 (HHV-6) genome and the unique long segment of the human cytomegalovirus genome are genetically colinear. Of particular interest is the identification of a region of local CpG dinucleotide suppression in the genome of HHV-6, a feature conserved in the genomes of human cytomegalovirus, murine cytomegalovirus, and simian cytomegalovirus, and a characteristic of the major immediate-early loci of these viruses. Adjacent to this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…The HHV-6 genome contains consensus binding sites for the transcription factors AP2 and NF-kB and contains KpnI repeat units believed to function as an immediate-early enhancer analogous to that of CMV [27]. This immediate-early enhancer performs a transactivating function for b-herpesviruses but is also capable of inducing the activation of the adenovirus, HTLV-1 and HIV gene enhancer promoter region.…”
Section: Introductionmentioning
confidence: 99%
“…The HHV-6 genome contains consensus binding sites for the transcription factors AP2 and NF-kB and contains KpnI repeat units believed to function as an immediate-early enhancer analogous to that of CMV [27]. This immediate-early enhancer performs a transactivating function for b-herpesviruses but is also capable of inducing the activation of the adenovirus, HTLV-1 and HIV gene enhancer promoter region.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that the HIV-1 LTR is transactivated by HHV-6 infection, as well as by HHV-6 genomic fragments [Lusso et al, 1989;Ensoli et al, 1989;Horvat et al, 1989;Geng et al, 1992;Martin et al, 1991;Wang et al, 1994;Horvat et al, 19911. Both major HHV-6 subgroups A and B exert this effect [Horvat et al, 1991;Garzino-Demo, unpublished results]. The present study demonstrates an enhanced transactivation of the HIV-1 LTR by TAT in combination with two HHV-6 genomic clones, suggesting that once initiated HIV-1 replication can be amplified in cells coinfected by HHV-6 and HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…A series of clinical and experimental observations indicates that HHV-6 may be a cofactor in the progression of HIV infection toward full-blown AIDS [Lusso et al, 19941. Like other herpesviruses HHV-6 was shown to transactivate the expression of the HIV-regulatory elements contained in the viral long terminal repeat (LTR) [Lusso et al, 7989;Ensoli et al, 1989;Horvat et al, 1989;Geng et al, 1992;Martin et al, 1991;Wang et al, 19941. By using HIV-LTR deletion mutants, the region of the LTR responsive to HHV-6 transactivation was mapped to the NFKB sites in the enhancer element of HIV-1 [Ensoli et al, 19891. In the case of HHV-6, however, such transactivating ability may be biologically significant because this virus can coinfect CD4+ T cells with HIV [Lusso et al, 19891 and, thereby, has the possibility to directly trigger or enhance the replication of HIV in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Sequences encoding the above ORFs were cloned into pUC19. The expression plasmid pBC-ORF contains the entire U89 ORF from the IE-A region of HHV-6A cloned into pBC/CMV [Martin et al, 1991]. The construction of the pHV6U86 plasmid containing the ORF U86 from the IE-A region of HHV-6A in pBluescriptSK vector has been described by Flamand et al [1998].…”
Section: Transfection Assaysmentioning
confidence: 99%
“…It has been shown that HHV-6 reactivates to active infections early in the course of HIV infection, and that lymph node infections at those early timepoints are predominantly due to HHV-6A [Knox and Carrigan, 1996]. The ®ndings that HHV-6 infections Di Luca et al, 1991] and cotransfections of subgenomic fragments of HHV-6 [Martin et al, 1991;Geng et al, 1992;Kashanchi et al, 1994;Nicholas and Martin, 1994;Thomson et al, 1994;Wang et al, 1994;Zhou et al, 1994] can activate transcription directed by the HIV-1 long terminal repeat (LTR) indicate the potential for HHV-6 to activate HIV-1 from latency and enhance its replication. In addition, the ability of HHV-6 to activate CD4 gene has been demonstrated in CD8 T lymphocytes [Lusso et al, 1991], natural killer cells [Lusso et al, 1993], and hematopoietic progenitor cells [Furlini et al, 1996].…”
Section: Introductionmentioning
confidence: 99%